2020
DOI: 10.1111/jocs.14858
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of fQRSTa in patients with aortic stenosis undergoing surgical aortic valve replacement

Abstract: Background Surgical aortic valve replacement (sAVR) is the ultimate therapy for severe aortic stenosis (AS) in suitable patients. Prognostic factors of sAVR are great interest in recent studies. Frontal QRS‐T angle (fQRSTa) is a novel marker of ventricular repolarization abnormalities. In this study, we aimed to investigate the prognostic value of fQRSTa in patients with severe symptomatic AS undergoing sAVR. Methods A total of 372 patients with severe degenerative AS who underwent successful sAVR were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Receiver-operating characteristic curves indicating the discriminative ability of the QT interval, Tp-e interval, Tp-e dispersion, Tp-e/QT ratio, and Tp-e/QTc ratio for mortality evaluated in terms of mortality. It was associated with worse prognosis in patients with AS undergoing surgical AVR 3. This supported our finding which showed that myocardial heterogeneity before operation was related with increased risk of mortality.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Receiver-operating characteristic curves indicating the discriminative ability of the QT interval, Tp-e interval, Tp-e dispersion, Tp-e/QT ratio, and Tp-e/QTc ratio for mortality evaluated in terms of mortality. It was associated with worse prognosis in patients with AS undergoing surgical AVR 3. This supported our finding which showed that myocardial heterogeneity before operation was related with increased risk of mortality.…”
supporting
confidence: 90%
“…1 In previous studies, several prognostic markers were described to predict high risk severe AS patient. 2,3 Ventricular repolarization abnormalities were studied in several cardiac diseases. Thus, it is well known that repolarization abnormalities were related with adverse cardiovascular events.…”
Section: Due To the Ageing Population Degenerative Aortic Valve Steno...mentioning
confidence: 99%
See 1 more Smart Citation
“…Severe aortic stenosis (AS) is a common heart valve disease, especially in the elderly population 1,2 . Considering the increase in the rate of elderly patients in the world population, especially in Europe, the prevalence of degenerative severe AS probably will increase in the near future 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Severe aortic stenosis (AS) is a common heart valve disease, especially in the elderly population. 1,2 Considering the increase in the rate of elderly patients in the world population, especially in Europe, the prevalence of degenerative severe AS probably will increase in the near future. 3,4 The most common treatment method used in these patients is surgical aortic valve replacement (SAVR), but the rate of transcatheter aortic valve replacement (TAVR) is increasing rapidly especially in the elder population.…”
Section: Introductionmentioning
confidence: 99%